A comprehensive review of traditional Chinese medicine in treating neuropathic pain - Naihua Hu; Jie Liu; Yong Luo; Yunxia Li (Heliyon, 2024)
Neuropathic pain (NP) is a common, intractable chronic pain caused by nerve dysfunction and primary lesion of the nervous system. The etiology and pathogenesis of NP have not yet been clarified, so there is a lack of precise and effective clinical treatments. In recent years, traditional Chinese medicine (TCM) has shown increasing advantages in alleviating NP. Our review aimed to define the therapeutic effect of TCM (including TCM prescriptions, TCM extracts and natural products from TCM) on NP and reveal the underlying mechanisms. Literature from 2018 to 2024 was collected from databases including Web of Science, PubMed, ScienceDirect, Google academic and CNKI databases. Herbal medicine, Traditional Chinese medicines (TCM), neuropathic pain, neuralgia and peripheral neuropathy were used as the search terms. The anti-NP activity of TCM is clarified to propose strategies for discovering active compounds against NP, and provide reference to screen anti-NP drugs from TCM. We concluded that TCM has the characteristics of multi-level, multi-component, multi-target and multi-pathway, which can alleviate NP through various pathways such as anti-inflammation, anti-oxidant, anti-apoptotic pathway, regulating autophagy, regulating intestinal flora, and influencing ion channels. Based on the experimental study and anti-NP mechanism of TCM, this paper can offer analytical evidence to support the effectiveness in treating NP. These references will be helpful to the research and development of innovative TCM with multiple levels and multiple targets. TCM can be an effective treatment for NP and can serve as a treasure house for new drug development.